Islamic Philosophy: Analytical Study of Figures and Their Thoughts - Ismi Ulfi Aoliyah; Didik Himmawan; Siti Nurjana; Luvia Hanum (Konsultan Jurnal Ilmiah Indonesia, 2024)
Islamic philosophy is a branch of philosophy that is closely related to Islamic teachings. This philosophy not only links human thinking with life, but also with the spiritual context of the Islamic religion. Islamic philosophy did not completely originate from Greek philosophy, but was also born from the teachings of Muslim philosophers in the Middle East. The purpose of this research is to find out analytical studies about figures and their thoughts. The research method used in this research is a qualitative method with a literature study approach, in the technique of reviewing and concluding various literature sources that are relevant to the topic under study. The results of this research are that Alkindi's philosophical thinking is focused on Al-Kindi being known as the